Effects of Atorvastatin and Pravastatin on Signal Transduction Related to Glucose Uptake in 3T3L1 Adipocytes - Akira Takaguri; Kumi Satoh; Mai Itagaki; Yukiko Tokumitsu; Kazuo Ichihara (Elsevier, 2008)
A number of patients with hyperlipidemia are prescribed 3-hydroxy-3-methylglutaryl-CoA reductase inhibitors that are concomitantly used along with the treatment of diabetes mellitus. The effects of atorvastatin and pravastatin on insulin-induced glucose uptake and the related signal transduction in 3T3L1 adipocytes were studied. 3T3L1 fibroblasts were differentiated into adipocytes, pretreated with atorvastatin or pravastatin, and then exposed to insulin. Glucose uptake and the amount of insulin signal proteins were measured. Atorvastatin significantly decreased insulin-stimulated 2-deoxyglucose uptake in 3T3L1 adipocytes associated with the prevention of translocation of GLUT4 into the plasma membrane. The amounts of Rab4 and RhoA that required lipid modification with farnesyl or geranylgeranyl pyrophosphate, in the membrane fraction were decreased by atorvastatin. Insulin-induced tyrosine phosphorylation of IRS-1 and serine/threonine phosphorylation of Akt were reduced by atorvastatin. Pravastatin did not modify these insulin-induced changes in the signal transduction. Inhibitors of the RhoA /Rho kinase system, C3 and Y27632, as well as atorvastatin reduced insulin-induced changes in signal transduction. Atorvastatin and pravastatin did not affect messenger RNA expression, protein level, and tyrosine phosphorylation of insulin receptors. In conclusion, hydrophobic atorvastatin decreases the glucose uptake by 3T3L1 adipocytes since it can enter the cell and prevents lipid modification of some proteins that are involved in the insulin signal transduction process. Keywords:: adipocyte, insulin, glucose, 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) reductase, signal transduction